Research on IQ imbalance estimation algorithm based on GSOP - Xian ZHOU; Tianyu GAO; Jiahao HUO; Xiaojie SHEN; Dongxu LU; Wei HUANGFU; Jiajing TU; Keping LONG (Tongxin xuebao)
In order to satisfy the demand of the efficiency and low cost measurement for high rate optical communication system,the IQ-ImEstimation algorithm was proposed for IQ imbalance estimation in the PDM-MQAM cohernt optical communication system based on GSOP.Two estimation schemes include amplitude impairment and phase impairment were designed by utilizing the power and correlation.Finally,a 34 GBaud PDM-MQAM system was simulated and experimentalized.The results indicate that the IQ-ImEstimation algorithm is accuracy and effective.